The HUBUNGAN ANTARA DERAJAT OSTEOARTRITIS DENGAN GAMBARAN USG TULANG RAWAN PADA PASIEN OSTEOARTRITIS LUTUT DI RSU AL FAUZAN PERIODE TAHUN 2016-2017: HUBUNGAN ANTARA DERAJAT OSTEOARTRITIS DENGAN GAMBARAN USG - Amalia, Riza; Supartono, Basuki; Satya, Ika; Wiyono, Sugeng (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2021)
Osteoarthritis is a degenerative joint disease which is related with the damage of cartilage. X-Ray is one of the osteoarthritis radiological examinations but only to see the damage of bone not cartilage. One of an effective examination to visualize the damage of cartilage is Ultrasound. The objective of this study is to determine the relation between osteoarthritis grading scale with cartilage ultrasonographic in knee osteoarthritis patients. This was a Cross-sectional study on 32 knee osteoarthritis patients based on Total Sampling technique at RSU Al Fauzan period of 2016-2017. Statistical analysis was performed using Fisher test showed there was a correlation between osteoarthritis grading scale with cartilage ultrasonographic. The conclusion in this study, there is a significant correlation between osteoarthritis grading scale with cartilage ultrasonographic in knee osteoarthritis patients. Keywords: Knee Osteoarthritis, Ultrasound, X-Ray